Adding a low-concentration sciatic nerve block to total knee arthroplasty in patients susceptible to the adverse effects of non-steroidal anti-inflammatory drugs (NSAIDs): a randomized controlled trial - Busara Sirivanasandha (BMC, 2021)
Abstract Background This study compared the effects of adductor canal blocks with those of a low concentration of popliteal-sciatic nerve block (SNB) and dexamethasone as an adjunctive technique for total knee arthroplasties (TKA) in patients susceptible to the adverse effects of NSAIDs. Methods A prospective, double-blinded, randomized controlled trial was performed in 50 patients susceptible to the adverse effects of NSAIDs undergoing unilateral TKAs. All patients received spinal anesthesia, adductor canal blocks, and periarticular infiltration. The 25 patients in the intervention group received SNB (0.125% bupivacaine [20 ml] and dexamethasone [5 mg]). Results The SNB group significantly had lower median resting pain scores at 6, 12, and 18 h: the control group, 1 (0–4.5), 3 (0–5), and 3 (2–5); the intervention group, 0 (0–0), 0 (0–3), and 1 (0–3); p-values, 0.012, 0.021, and 0.010, respectively. Movement-evoked pain scores at 6, 12, and 18 h were also lower: control group, 3 (0–5.5), 5 (2.5–6.5), and 7 (4–9); intervention group, 0 (0–1.5), 2 (0–4), and 3 (2–5); p-values, 0.019, 0.005, and 0.001, respectively. There were no differences in motor function. Moreover, the mean morphine consumption 24 h was also reduced in the SNB group: control group, 3.80 ± 2.48 mg; intervention group, 1.96 ± 2 mg; p-value, 0.005. Conclusion For patients susceptible to the adverse effects of NSAIDs, a low concentration of SNB and dexamethasone is an effective adjunctive technique for early postoperative pain control (especially on movement) following TKAs, without an increase in motor weakness. Trial registration ClinicalTrials.gov , NCT03486548 , Registered 3 April 2018.